Shaping Visual Personality: the Role of Character Make-up and Body Shape in Visualizing Warrior Characters in Indonesia Silat Film - Puspitasari, Feny; Piliang, Yasraf Amir; Kahdar, Kahfiati; Waskita, Dana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The warrior character is an important element in the storyline and a narrative developer in silat films. The warrior is the main character with distinctive characteristics in Silat's stories, especially the visual character. Talent is supported by make-up with a body shape that tends to be static to differentiate the role. This research explores the relationship between character make-up, body shape, and character, including stereotypes of warrior characters in silat films. This research used content analysis with a physiognomy theory approach to read the characters in the characters' make-up. In addition, somatotype theory is used to analyze characters based on body shape. A case study was conducted on the Indonesian Silat film Wiro Sableng (2018), focusing on the main hero, heroine, and villain characters and representing three body types.